Respuesta :
Answer:
(x+4)(x-3) or A
Step-by-step explanation:
I'm going to assume that you meant to write x² and not x2
which means we have
x²+x-12
and we need to factor this
to do this we need two numbers that add up to 1 (b) but mulitply to -12 (a*c)
our two numbers are
4, -3
Which means the answer is
(x+4)(x-3)
[tex]{ \large{ \bf{f(x) = x {}^{2} + x - 12}}}[/tex]
[tex]{ \large{ \bf{zeros = \dfrac{ - b± \sqrt{b {}^{2} - 4ac } }{2a} }}}[/tex]
[tex]{ \large{ \bf{zeros = \dfrac{ - 1± \sqrt{1 {}^{} + 48 } }{2} }}}[/tex]
[tex]{ \large{ \bf{zeros = \dfrac{ -1± 7 }{2} }}}[/tex]
[tex]{ \large{ \bf{➢ \: \: zeros = - 4 \: \: and \: 3 }}} \: \: \: \: \: \: (ans)[/tex]